Analysis of Land Use Changes In the period 2018-2005 in Nazloo District of Urmia City - Sahar Mehrran; Ali Akbar Taghilou; Khadijeh Javan (تحقیقات کاربردی علوم جغرافیایی)
Analysis of land use change in Nazlou district of Urmia in the 2005-2018 time series Abstract Population growth, increased prosperity, the spread of technology, and the improper use of land have in recent decades imposed many changes on land. Nazlou district in Urmia city has been exposed to many changes due to its favorable natural conditions, location in the development paths of Urmia-Cir and Urmia-Bazargan, establishment of numerous industrial estates and so on. So planning to manage these changes requires studying land use changes. The purpose of this study was to detect land use changes in Nazlou district in Urmia city using Landsat TM and OLI satellite images by Object Oriented Classification. Also, two methods of change detection and change intensity index in land use change monitoring were used to investigate the severity and trend of land use changes. This study was descriptive and analytical and data collection was done by documentary method. The survey showed that during the study period (2005-2018) of the total area of ​​77498.37 hectares, the total area under study was approximately 25981.56 ha (33.52%). The highest level of change in 2005 relates to the level of the horticulture, with its downward trend in 2018. In contrast, changes in rangeland and dryland land use have an increasing trend, respectively.